Large Eddy Simulation of a laboratory-scale gas-assisted pulverized coal combustion chamber under oxy-fuel atmospheres using tabulated chemistry. (15th July 2020) - Nicolai, H.; Kuenne, G.; Knappstein, R.; Schneider, H.; Becker, L.G.; Hasse, C.; Mare, F. di; Dreizler, A.; Janicka, J.
Abstract: This paper analyses a new gas-assisted pulverized coal combustion chamber, specially designed for the validation of numerical models under oxy-fuel atmospheres. For this purpose, an overall method is developed based on Large Eddy Simulation (LES) for oxy-fuel pulverized coal combustion chambers. One essential aspect of this is the embedding of a 4D Flamelet Generated Manifold (FGM) table coupled with an artificially thickened flame (ATF) model in the Euler-Lagrange (EL) framework. The four dimensions of the generated manifold represent the finite rate chemistry, mixing of volatiles, and char products and heat losses in the gas phase. Before the model is applied in the combustion chamber, its validity is demonstrated utilizing verification cases. Subsequently, the simulation results of the combustion chamber are validated and discussed with the help of the available measurement data. Operating points with increasing complexity are investigated, starting with a single-phase case that analyzes the reproduction of the assisting methane flame based on tabulated chemistry coupled with ATF. For the validation process, velocity fields from Particle Image Velocimetry (PIV) are used as well as flame positions from planar laser-induced fluorescence of the OH radical (OH-PLIF). Subsequently, operating conditions using different coal mass flows are investigated. To validate the flame stabilization mechanism, velocity data for the near burner region are available. Further examinations of the gas-assisted coal flame are carried out, in particular the influence of the coal particles on the flame stabilization mechanism is carried out.